Konseling Kelompok Menggunakan Teknik Self Control Untuk Mencegah Stres Menghadapi Ujian Nasional - Novi Andriati; Novi Wahyu Hidayati (Manajemen Pendidikan, 2021)
Stress is a non-specific body response to any burden over it, stress is a physical reaction to the problems of life experienced. The purpose of this research is the implementation of a group counseling service with self-control technique to prevent stress facing national exam-based computer students of Grade XII SMA cooperative Pontianak. This method of research is action research, the form of research is the study of Action guidance and Counseling (PTBK). Data collector techniques used (1) direct communication techniques, and (2) indirect communication techniques. The data collector tools (1) Interview guide and (2) psychological scale. The research was conducted in class XII of Pontianak Cooperative High School with a total of 12 members, taking the subject of research purposive sampling from the results of the distribution of stress scales. Research results: Students ' stress attitudes in facing national computer-based exams with a percentage of 26.4%, the process of implementing group counseling with self- control techniques in preventing stress facing national computer-based exams covering the formation phase, switching stage, activity stage, and closing stage. Stress facing a national exam-based computer can be reduced using counseling group with self-control technique with a percentage of 17.9%.